Estudo numérico-experimental do colapso de tubos de revestimento e produção sob tração axial e pressão externa - Silva, Eduardo Felipe Pereira da (2018)
The cost reduction of oil wells can be achieved with the proper selection of the casing and tubing. The objective of this dissertation is to evaluate the collapse equations for OCTG pipes proposed in the current standard ISO 10400 / API TR 5C3 for combined loads of external pressure and axial tension. A nonlinear numerical model based on the finite element method was developed in the commercial program ABAQUS to evaluate the effect of combined loads on collapse pressure. The effect of some parameters such as magnitude of axial tension, ratio D/t and initial ovalization were studied in the model. In addition, experimental tests were performed on a small scale with 316L stainless steel pipes with two different D/t ratios (15 and 24) for calibration of the numerical model. This small scale study was developed from the fullscale study with J55 casing tubes to analyze the effect of higher tensile loads on collapse pressure. The experimental results confirmed that the collapse pressure was reduced by 32% for pipes with a D/t ratio of 15, whereas for the D/t ratio of 24 the reduction was 13,5% with 60% of yield tension. Besides, it was possible to verify that the design equations and the ultimate collapse equations presented in Annex F of ISO 10400 obtained better performance to predict collapse pressure under combined loads when compared with the historical equations of chapter 8 of the same standard.